Successful per-vaginal delivery of a schistosomus reflexus monster fetus in a crossbred cow – a case report - Pramod Kumar; Satish; Bhanu Prakash; Rajendra Mehra; G. Sasi; Tipu Sultan; Lakhan Ram Yadav; Amit Narwal (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Nine years old crossbred cow was presented to the TVCC, CVAS, Bikaner with dystocia of about 9 hours duration. Intestine parts and abdominal visera of the fetus were protruded from the vulva of the cow. Vaginal examination confirmed deformed fetus (schistosomus reflexus) in the pelvic cavity. The dystocia was relieved through vaginal passage by mutation and forced traction.